4D flow imaging with 2D‐selective excitation. Issue 3 (19th April 2019) - Wink, Clarissa; Ferrazzi, Giulio; Bassenge, Jean Pierre; Flassbeck, Sebastian; Schmidt, Simon; Schaeffter, Tobias; Schmitter, Sebastian
Abstract : Purpose: 4D flow MRI permits to quantify non‐invasively time‐dependent velocity vector fields, but it demands long acquisition times. 2D‐selective excitation allows to accelerate the acquisition by reducing the FOV in both phase encoding directions. In this study, we investigate 2D‐selective excitation with reduced FOV imaging for fast 4D flow imaging while obtaining correct velocity quantification. Methods: Two different 2D‐selective excitation pulses were designed using spiral k‐space trajectories. Further, their isophase time point was analyzed using simulations that considered both stationary and moving spins. On this basis, the 2D‐selective RF pulses were implemented into a 4D flow sequence. A flow phantom study and seven 4D flow in vivo measurements were performed to assess the accuracy of velocity quantification by comparing the proposed technique to non‐selective and conventional 1D slab‐selective excitation. Results: The isophase time point for spiral 2D‐selective RF pulses was found to be located at the end of excitation for both stationary and moving spins. Based on that, 2D‐selective excitation with reduced FOV allowed us to successfully quantify velocities both in a flow phantom and in vivo. In a flow phantom, the velocity difference Δ v ¯ = 0.8 ± 5.3 cm/s between the smaller reduced FOV and the reference scan was similar to the inter‐scan variability of Δ v ¯ = - 1.0 ± 2.3 cm/s . In vivo, the differences in flow ( P = 0.995) and flow volume ( P = 0.469) between the larger reduced FOV and the reference scan were non‐significant. By reducing the FOV by two‐thirds, acquisition time was halved. Conclusion: A reduced field‐of‐excitation allows to limit the FOV and therefore shorten 4D flow acquisition times while preserving successful velocity quantification.